2016
DOI: 10.2737/psw-gtr-252
|View full text |Cite
|
Sign up to set email alerts
|

Restoring California black oak ecosystems to promote tribal values and wildlife

Abstract: In accordance with Federal civil rights law and U.S. Department of Agriculture (USDA) civil rights regulations and policies, the USDA, its Agencies, offices, and employees, and institutions participating in or administering USDA programs are prohibited from discriminating based on race, color, national origin, religion, sex, gender identity (including gender expression), sexual orientation, disability, age, marital status, family/parental status, income derived from a public assistance program, political belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 106 publications
0
28
0
Order By: Relevance
“…In northwestern California, Franklin et al (2000) found that the juxtaposition of nesting with non‐nesting habitat for spotted owls increased fitness presumably by facilitating access to woodrats as prey. Moreover, promoting woodrat food resources such as masting California black oak and nesting resources such as cavities in snags and large diameter logs (Innes et al 2007) would not only boost woodrat abundance, but would also increase habitat suitability for other species such as pacific fisher ( Pekania pennanti ) and owls (Long et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northwestern California, Franklin et al (2000) found that the juxtaposition of nesting with non‐nesting habitat for spotted owls increased fitness presumably by facilitating access to woodrats as prey. Moreover, promoting woodrat food resources such as masting California black oak and nesting resources such as cavities in snags and large diameter logs (Innes et al 2007) would not only boost woodrat abundance, but would also increase habitat suitability for other species such as pacific fisher ( Pekania pennanti ) and owls (Long et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…3, the apparent slopes of the lines are influenced by the intercept, and odds ratios should be used to determine the difference in owl selection at low vs. high elevations for both variables. but would also increase habitat suitability for other species such as pacific fisher (Pekania pennanti) and owls (Long et al 2016).…”
Section: Management Implicationsmentioning
confidence: 99%
“…All rights reserved Long-term fire exclusion leads to the loss of informational (species life history traits) and material (biotic and abiotic structures such as seeds and nutrients) legacies (Johnstone et al 2016) that may compromise fire-dependent diversity and the capacity of forested ecosystems to resist or recover after wildfires, especially under climate change (Franklin et al 2000, Krawchuk et al 2020). Among these legacies are mature and old trees, in particular, open-canopy forests of mature and old conifers and hardwoods which provide unique ecosystem functions and which were once substantially more prevalent (Spies et al 2006, Kolb et al 2007, Long et al 2015, Franklin et al 2018, Hanberry and Dumroese 2020. As climate continues to warm and burned area increases, early seral habitat will likely be created in abundance.…”
Section: Accepted Articlementioning
confidence: 99%
“…Parks, Holsinger, Miller, & Parisien, 2018, 8. Westerling, 2018 manage ecological communities today (Long et al, 2016;Long, Goode, Gutteriez, Lackey, & Anderson, 2017). However, the region is recovering from over a century of Euro-American fire suppression concomitant with the exclusion of Indigenous cultural burning practices, which enabled excess vegetation growth, fuel accumulation (Stephens, Martin, & Clinton, 2007), and ecosystem homogenization (Koontz et al, 2020), all of which contributed to a departure from the Sierra Nevada fire regime that existed prior to modern-day anthropogenic climate change.…”
Section: Define Planning Scopementioning
confidence: 99%